Alienation Divorced alienation (Journal Of Educational and Psychological Researches, 2013)
The divorce is one of the important problem that prominence in Iraq it needs a remedy speedily .This problem appears specially at the war of 2003 , it is effected on culture and it trances through communications tools , internet and satellite .Supreme judicial council recorded about (41536) divorced cases , whereas the rate of this number arise to (87.530) through 2012 , in the same time the Iraqi courts recorded about 20%-30% of wedding cases .The two researchers focused in their study on the concept of Alienation as a basic variable through its enhancing on the psychological health for divorces , in which they take this sense to connect it with their shortage that reflect negatively on their psychological and social situation of divorced woman .Goals of study :Measuring of alienation to divorce woman .The result :   The research has statistically significant according to its analytic of sample .There is not any appearance of difference of divorced woman alienation according to age , children number , marriage period and the reason of divorce .There are statistically differences of divorced alienation according to variable occupation .There are statistically differences of alienation according to variable academic achievement . There are statistically differences according to economical scale .The research concluded with set of proposals and recommendations which are : Improve the economic situation for this segment .Emphasis on the role of the media to correct society's perception of the concept of divorce.Open guidance centers to reduce from divorce phenomenon